ANTECEDENTS AND CONSEQUENCES OF CUSTOMER SATISFACTION AND LOYALTY: AN EMPIRICAL STUDY OF POPULAR CAFE IN MANDALAY, MYANMAR - Kyaw, May Thu; Chaipoopirutana, Sirion (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
This research aims to examine the factors influencing customer satisfaction and loyalty towards the popular cafe in Mandalay, Myanmar. The researcher applied the factors, including perceived customer to employee interaction, perceived service quality, and perceived value. The sample size of this study is 400, and questionnaires are distributed at Mingalar Mandalay Complex. In this study, the researcher applied non-probability sampling methods, including purposive and convenience sampling techniques. The researcher also used the five-point Likert scale, designed as research instruments. To test the hypotheses, the researcher used both simple linear regression and multiple linear regression to analyze and calculate the data. Based on the research finding, the researcher found that perceived service quality significantly influenced perceived value and perceived customer to employee interaction, and perceived value significantly influenced customer satisfaction except for perceived service quality. Furthermore, perceived value and customer satisfaction significantly influenced customer loyalty.